2014
DOI: 10.1007/s10597-014-9764-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Web-Based Community Reinforcement Approach for Substance Use Disorders with Treatment-Seeking American Indians/Alaska Natives

Abstract: Longstanding disparities in substance use disorders and treatment access exist among American Indian/Alaska Natives (AI/AN). Computerized, web-delivered interventions have potential to increase access to quality treatment and improve patient outcomes. Prior research supports the efficacy of a web-based version (Therapeutic Education System [TES]) of the Community Reinforcement Approach to improve outcomes among outpatients in substance abuse treatment; however, TES has not been tested among AI/AN. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 44 publications
1
47
0
1
Order By: Relevance
“…The culturally adapted MICRA appears to be effective as was a previous implementation of MI and aspects of CRA in Project COMBINE with general U.S. samples ( Anton et al, 2006 ). Results from the current study are further corroborated by a previous study of internet-based CRA delivered to urban AIs that found high rates of acceptability for CRA, though participants noted several suggestions to increase cultural relevance ( Campbell et al, 2015 ). For AI/ANs who are facing substantial substance use related health disparities, cultural adaptations of EBTs represent an important avenue for reducing these health disparities.…”
Section: Discussionsupporting
confidence: 86%
“…The culturally adapted MICRA appears to be effective as was a previous implementation of MI and aspects of CRA in Project COMBINE with general U.S. samples ( Anton et al, 2006 ). Results from the current study are further corroborated by a previous study of internet-based CRA delivered to urban AIs that found high rates of acceptability for CRA, though participants noted several suggestions to increase cultural relevance ( Campbell et al, 2015 ). For AI/ANs who are facing substantial substance use related health disparities, cultural adaptations of EBTs represent an important avenue for reducing these health disparities.…”
Section: Discussionsupporting
confidence: 86%
“…As shown in Table 3, 11 (34%) sources were from the USA [15][16][17][18][19][20][21][22][23][24][25] and nine (28%) sources were from New Zealand [26][27][28][29][30][31][32][33][34], with the remainder from Australia (12, 38%) [35][36][37][38][39][40][41][42][43][44][45]. As there were no studies from Canada, the findings reported from here on pertain to New Zealand, the USA and Australia.…”
Section: Characteristics Of Sourcesmentioning
confidence: 84%
“…Five of the 11 integrated blended interventions with an Internet focus aimed at improving the delivery of evidence-based treatment in primary care [ 31 , 48 , 50 , 65 , 72 ], for instance, by assisting GPs in providing evidence-based mental health care programs [ 65 ]. Three of the studies aimed at integrating face-to-face sessions to maximize the effectiveness of iCBT [ 19 , 64 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using blended interventions to improve the delivery of evidence-based treatment in primary care has been successful in acceptability and in reducing symptomatology [ 31 , 48 , 50 , 65 , 72 ]. However, two controlled studies [ 50 , 65 ] could not show a superiority of the blended intervention over an active nonblended control group.…”
Section: Resultsmentioning
confidence: 99%